The effects of the presence of others during a rowing exercise in a virtual reality environment. (January 2016) - Murray, Edward G.; Neumann, David L.; Moffitt, Robyn L.; Thomas, Patrick R.
Abstract: Objectives: The aim of the study was to test the performance, motivational, and affective impact of aerobic exercise within an immersive virtual reality environment experienced alone or with another individual. Design: Sixty female participants aged 18–30 years were assigned to one of three conditions: no virtual reality (NVR), individual virtual reality (IVR), or companion virtual reality (CVR). Method: Participants completed 9 min of self-paced rowing on an ergometer without any visual input or performance feedback (NVR), individually within a virtual reality environment (IVR), or within a virtual reality environment that included a companion depicted as an avatar (CVR). Results: The two virtual reality groups rowed a further distance and at a higher power output than the NVR group. Furthermore, the CVR group outperformed the IVR group in distance and had a higher heart rate. Participants in the virtual reality groups did not perceive themselves to be exerting more physical effort and rated the task as more enjoyable than participants in the NVR group. Conclusions: Virtual reality improves performance and the affective response to aerobic exercise, and performance effects are further enhanced by the presence of others in the virtual environment. Highlights: Rowing in a virtual reality environment increased performance and enjoyment. Performance effects were enhanced by the inclusion of a virtual team-mate. Virtual reality can improve physical and affective aerobic exercise outcomes.